Silicon-Based On-Chip Light Sources: A Review - Yongqi Yang; Jiaqi Yang; Zhouyang Cheng; Shuyan Zhang; Zhen Yang; Shengchuang Bai; Rongping Wang (Photonics)
Silicon-based on-chip light sources are important since they can provide a compact solution for various applications in the field of high-speed optical communications, high-precision sensing, quantum information processing, and so on. We review the progress of silicon-based on-chip light sources in various materials. We provide some key parameters like pump thresholds, output powers, and pump schemes of on-chip lasers based on various materials. Finally, we point out the existing issues in the current investigations and possible solutions in the future.